2017
DOI: 10.1038/srep44587
|View full text |Cite
|
Sign up to set email alerts
|

Composition and temperature-dependent phase transition in miscible Mo1−xWxTe2 single crystals

Abstract: Transition metal dichalcogenides (TMDs) WTe2 and MoTe2 with orthorhombic Td phase, being potential candidates as type-II Weyl semimetals, are attracted much attention recently. Here we synthesized a series of miscible Mo1−xWxTe2 single crystals by bromine vapor transport method. Composition-dependent X-ray diffraction and Raman spectroscopy, as well as composition and temperature-dependent resistivity prove that the tunable crystal structure (from hexagonal (2H), monoclinic (β) to orthorhombic (Td) phase) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 52 publications
(75 reference statements)
5
38
2
Order By: Relevance
“…13c ). The reason why WS 2 was not produced at this stage is that the bond energy of Sn–S was likely to be lower than that of W–S due to the larger ionic radius of Sn 4+ compared to that of W 4+ 50 , 51 . As the reaction proceeded further, the amount of the Sn 0.17 WO 3 nanorods decreased, and nanosheets started to form on the surfaces of the SnS 2 nanoplates (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13c ). The reason why WS 2 was not produced at this stage is that the bond energy of Sn–S was likely to be lower than that of W–S due to the larger ionic radius of Sn 4+ compared to that of W 4+ 50 , 51 . As the reaction proceeded further, the amount of the Sn 0.17 WO 3 nanorods decreased, and nanosheets started to form on the surfaces of the SnS 2 nanoplates (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This hysteretic behavior has already been reported 76 − 80 and is a signature of a phase transition between the room-temperature metastable monoclinic phase (1T′) and the orthorhombic (T d ) phase, which is stable at lower temperature. 81 , 82 For further investigation of this signature, Raman spectroscopy was also carried out at different temperatures. It has in fact been reported that due to the change of symmetry from 1T′ to T d structure, this phase transition is also accompanied by a splitting of the A g peak at 129 cm –1 (also known as the P 6 peak), in P 6A and P 6B peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison to experimental results is hindered by the fact, that to the best of our knowledge, all the experimental T'-Mo (1−x) W x Te 2 alloy results are from bulk samples [4,35,36,65]. Monolayer data is only available for pure MoTe 2 and WTe 2 [57][58][59].…”
Section: B T'-(mow)te2mentioning
confidence: 99%